Kualitas Pelayanan Publik Pada SMK Plus Pontren di Kabupaten Garut - Asep Dadang (Madani: Jurnal Ilmiah Multidisiplin, 2022)
Education has a very significant meaning for humans. Achievement education must of course go through a very long process which is supported by certain stages. To realize achieving education, of course it must be through public policy as the basis for the establishment of an educational institution and as a form of public service. Quality of Education Services at Vocational School Plus Pontren in Garut Regency, with research locations at Vocational School Plus Pontren Qurrota A'yun, Samarang District, Vocational School Plus Pontren Alfalah Biru, Tarogong District and Vocational School Plus Pontren Fauzaniyah, Sukaresmi District, Garut Regency. To realize the quality of educational services requires Human Resources (HR) qualifications which contain knowledge as the basis for excellence and commendable moral values as the basis for personality. These Human Resources (HR) qualifications can be realized through an integrated educational institution which includes a technology-based curriculum and a religion-based curriculum.